Fostering Kalanamak rice farmer’s resilience and profitability in India by integrating local knowledge into the seed system and markets - Nayak, Swati; Nath, Anirban; Shukla, Sarvesh; Hossain, S. K. Mosharaf; Badoni, Saurabh; Singh, Vivek Kumar (Frontiers in Sustainable Food Systems, 2025)
IntroductionKalanamak, an aromatic rice landrace (Oryza sativa L.) traditionally cultivated by indigenous farmers in the Terai belt of Uttar Pradesh, India, has seen a resurgence following the development of improved accessions with higher productivity and market potential. Like other aromatic landraces in India, Kalanamak holds deep socio-economic value, prized for its agroecological resilience, cultural identity, culinary heritage, and role in rural livelihoods.MethodsThe current study focused on three key aspects: (1) comparing the performance of traditional and improved Kalanamak cultivars within the Geographically Indicated (GI) area, (2) mapping the seed and milled rice value chain, and (3) building farmer capacity for quality seed production of improved Kalanamak varieties. Eleven traditional accessions and three improved semi-dwarf varieties of Kalanamak were evaluated through replicated multi-year trials in the GI area. Additionally, a comprehensive value chain assessment of the Kalanamak seed and rice market was conducted through participatory rural appraisal and in-depth interviews with 50 value chain actors, including smallholder farmers, seed growers, millers, and community-based organizations (CBOs).ResultsSemi-dwarf cultivars such as Bauna Kalanamak 101, Bauna Kalanamak 102, and Kalanamak Kiran showed higher mean yield compared to the traditional accessions; however, the differences in yield were statistically non-significant. Findings revealed a hybrid seed network where decentralized farmer-to-farmer exchange coexists with collective-led procurement and emerging private sector channels. To strengthen this evolving system, targeted capacity building in 15 villages in terms of quality seed production was ensured—enhancing farmer skills in varietal selection, purity maintenance, and post-harvest handling—leading to the production of 6,800 kg of quality seeds and improved access to high-performing Kalanamak varieties. Profitability assessment compared traditional and improved cultivars under organic and inorganic practices. Semi-dwarf Kalanamak variants under organic cultivation showed the highest profitability (B:C ratio 3.92), outperforming traditional varieties and inorganic systems. Sensitivity analysis further revealed that semi-dwarf systems remained the most resilient under adverse cost–benefit shifts, consistently maintaining BCRs above 2.0.Discussion and conclusionThe results affirm that integrating farmer-led seed systems with scientifically validated accessions and localized training can enhance profitability, strengthen seed sovereignty, and revitalize the Kalanamak rice economy in the GI areas. The study underscores the importance of combining participatory approaches with varietal improvement and seed system strengthening to sustain the cultural and economic legacy of Kalanamak rice.